Active earth pressures for non-planar to planar slip surfaces considering soil arching. Issue 7 (2nd October 2020) - Khosravi, Mohammad Hossein; Kargar, Ali Reza; Amini, Mehdi
ABSTRACT: The soil arching behind a rigid retaining wall was considered using log-spiral and parabolic slip surfaces with a changeable curvature defined by a new parameter Rpl so called "planar ratio of slip surface". By increasing Rpl, the difference between log-spiral and parabolic slip surfaces reduced. When Rpl approached one, both slip surfaces reduced to a planar slip surface. Moreover, equations for the estimation of earth pressure in the failure zone behind the wall were developed. It was observed that as the wall height decreased, the curvature of the slip surfaces behind the wall decreased leading to a larger value of Rpl . Therefore, the assumption of a planar slip surface behind retaining walls can be realistic only for shallow walls. As the wall height increases, the slip surface appeared to be more non-planar. The results of the developed formulations showed a good agreement with the experimental data.